Cue strength in second-language processing: An eye-tracking study. Issue 3 (March 2015) - Tuninetti, Alba; Warren, Tessa; Tokowicz, Natasha
This study used eye-tracking and grammaticality judgement measures to examine how second-language (L2) learners process syntactic violations in English. Participants were native Arabic and native Mandarin Chinese speakers studying English as an L2, and monolingual English-speaking controls. The violations involved incorrect word order and differed in two ways predicted to be important by the unified competition model [UCM; MacWhinney, B. (2005). A unified model of language acquisition. In J. F. Kroll & A. M. B. de Groot (Eds.), Handbook of bilingualism: Psycholinguistic approaches (pp. 49–67). Oxford: Oxford University Press.]. First, one violation had more and stronger cues to ungrammaticality than the other. Second, the grammaticality of these word orders varied in Arabic and Mandarin Chinese. Sensitivity to violations was relatively quick overall, across all groups. Sensitivity also was related to the number and strength of cues to ungrammaticality regardless of native language, which is consistent with the general principles of the UCM. However, there was little evidence of cross-language transfer effects in either eye movements or grammaticality judgements.